Design of Frequency Conversion and Soft Start Cooperative Control System for Mine Fan. Issue 4 (March 2021) - Zhang, Hongkui; Huang, Xiaoting; Yang, Guangyu; Li, Tingliang; Ma, Long; Chen, Lei
Abstract: In order to improve the safety and reliability of mine fan control system and realize remote control in dual operation modes, a cooperative control system of frequency conversion and soft start of mine fan was developed based on PLC. On the basis of analyzing the position of coal mine in China's economic development and the role of coal mine ventilation system, this paper expounds the working principles of mine soft starter and mine frequency converter, and designs a cooperative control system of mine fan frequency conversion and soft start based on PLC, which realizes remote control of mine fan starting, running and stopping, and has the functions of voltage, current, wind speed and air volume parameter monitoring and fault protection.